1979
DOI: 10.1080/02791072.1979.10471408
|View full text |Cite
|
Sign up to set email alerts
|

PCP (Phencyclidine): An Update

Abstract: The steady rise in the promiscuous use of phencyclidine (PCP) as a "recreational" drug has recently gained nationwide attention because of the numerous violent and/or bizarre incidents caused by the use of this drug. Because the media often exaggerate reports of bizarre and violent behavior to make a "good" story, the potential PCP user may be tempted to ignore the media warnings. In the case of PCP, however exaggerated the story, a real danger does exist. So, despite numerous newspaper, radio and television w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
0
41
0
1
Order By: Relevance
“…The first group to test this hypothesis used the phencyclidine (PCP) model of schizophrenia. PCP, an NMDA antagonist induces acute psychosis in humans 95 and can produce schizophrenia-like deficits in rodents 22,23 . Using the sub-acute PCP model, Tanaka and colleagues demonstrated that deficits in novel object recognition and prepulse inhibition were prevented by transplanting MGE tissue into the medial prefrontal cortex (mPFC) of newborn animals 96 .…”
Section: Using Interneurons To Treat Schizophreniamentioning
confidence: 99%
“…The first group to test this hypothesis used the phencyclidine (PCP) model of schizophrenia. PCP, an NMDA antagonist induces acute psychosis in humans 95 and can produce schizophrenia-like deficits in rodents 22,23 . Using the sub-acute PCP model, Tanaka and colleagues demonstrated that deficits in novel object recognition and prepulse inhibition were prevented by transplanting MGE tissue into the medial prefrontal cortex (mPFC) of newborn animals 96 .…”
Section: Using Interneurons To Treat Schizophreniamentioning
confidence: 99%
“…In their seminal review, Jentsch and Roth (1999) describe that the positive symptoms dominate after acute intake of PCP/ketamine, whereas after chronic intake, negative symptoms become more obvious. Garey (1979) outlined that the effects of chronic PCP use seem to be twofold: severe depression with suicidal thoughts and numerous violent, agitated behavioural patterns. De Angelis and Goldstein (1978) also describe anxiety as an additional symptom.…”
Section: Introductionmentioning
confidence: 99%
“…Early support for the glutamate hypothesis of schizophrenia came from suggestions that non-competitive antagonists of the NMDA receptor [such as phencyclidine (PCP), dizocilpine (or MK-801), and ketamine] partially mimic both positive and negative symptoms of schizophrenia when administered to healthy humans (Luby et al, 1959;1962;Allen and Young, 1978;Garey, 1979;Snyder, 1988;Javitt and Zukin, 1991). While there are reports of the NMDA antagonist ketamine disrupting PPI in healthy humans (Karper et al, 1995), there have also been reports of ketamine administration resulting in a slight increase in PPI (Duncan et al, 2001;Abel et al, 2003).…”
Section: Ionotropic Glutamate Receptors and Ppimentioning
confidence: 97%